Building Roads to Democracy? The Contribution of the Peru Rural Roads Program to Participation and Civic Engagement in Rural Peru - McSweeney, Catherine (World Bank, Washington, DC, 2012)
Projects involving community participation often give communities responsibility to identify, prioritize, plan and implement small-scale investments. While the approach generates high ownership and relevance, it has often been considered inappropriate for large infrastructure projects with requirements of economies of scale, technical standards and efficiency. The Peru Rural Roads Program (PCR) finds the right balance between the two approaches by integrating community participation in a large-scale rural roads program with best practices, both in terms of flexibility and adaptability in project implementation, increased ownership and efficient management of road assets. Its positive impacts on rural transport, local economic development and local governance in Peru have earned it best practice awards from Peruvian civil society, from the Inter-American Development Bank and from the World Bank (President's Award for Excellence 2001). This note highlights its innovative design features and focuses on its impact on governance. Governance outcomes that are particularly highlighted include strengthening integrated participatory development planning, increasing local institutional capacity, promoting transparency in local governance and fostering civic engagement.